Efeito de fosfatos naturais parcialmente acidificados com H3PO4, HCL e H2SO4 em sorgo granífero (Sorghum bicolor (L) Moench): I- Peso da parte aérea, das raízes e total - Franco , Marcelo; Braga , J M; Thiébaut, J T L (Revista Ceres, 2025)
Experiments were carried out to study the effects of low acidification of phosphates from Patos and Araxa, Minas Gerais, on dry matter production in plants on cerrado soils. The phosphates were treated with phosphoric, hydrochloric and sulphuric acids. Trials were run in the greenhouses of the Federal University of Viçosa, Viçosa, Minas Gerais, Brazil.